Home Care Services and Acceptability of Home Care Services in Metro Cities of India - Kumar , Anil; Shah , Vinesh; Varambally , KVM; Jeremiah , M S; Chaudhari , Vipul P (National Journal of Community Medicine, 2012)
Objective: To find out the perception of people in terms of merits and acceptability of home care services. Methods: A sample of 400 households and 400 experts was covered in four metropolitan (Metro) cities viz. Mumbai, Delhi, Kolkata and Chennai. It involved the study of perceptions and acceptability of Home Care Services. The data was collected using a self-administered questionnaire given to both the experts and the households. The sampling for the study on home care services was done through Convenience Sampling Method. The basic statistical calculations were worked out performed using SPSS version 15. Results: The households who had filled the questionnaire were of an average age 40-49 years (66 %) and 34 % of them were above the age of 60 years. 59% of the households were females. About 87 % of the households had health insurance. 94.50 % of households opined that doctors don‘t spend sufficient time with them to explain the progress and condition of the patient. Almost all (99.75%) households said that home care services were more comfortable and provided a particularly familiar environment. About 98.50 % of experts viewed that home care services could provide better and emotional support to patients which helps them to recover faster. Conclusion: Home Care Services are advantageous and beneficial to people in urban parts since it brings sizeable beneficial impact over hospital care. However, Home Care Service cannot be a complete alternative to hospital care.